Disordered interdomain region of Gins is important for functional tetramer formation to stimulate MCM helicase in Thermoplasma acidophilum. Issue 3 (4th March 2015) - Ogino, Hiromi; Ishino, Sonoko; Oyama, Takuji; Kohda, Daisuke; Ishino, Yoshizumi
Abstract: The eukaryotic MCM is activated by forming the CMG complex with Cdc45 and GINS to work as a replicative helicase. The eukaryotic GINS consists of four different proteins to form tetrameric complex. In contrast, the TaGins51 protein from the thermophilic archaeon, Thermoplasma acidophilum forms a homotetramer (TaGINS), and interacts with the cognate MCM (TaMCM) to stimulate the DNA-binding, ATPase, and helicase activities of TaMCM. All Gins proteins from Archaea and Eukarya contain α-helical A- and β-stranded B-domains. Here, we found that TaGins51 forms the tetramer without the B-domain. However, the A-domain without the linker region between the A- and B-domains could not form a stable tetramer, and furthermore, the A-domain by itself could not stimulate the TaMCM activity. These results suggest that the formation of the Gins51 tetramer is necessary for MCM activation, and the disordered linker region between the two domains is critical for the functional complex formation. Graphical Abstract: : The disordered linker region, but not the B-domain, of Thermoplasma acidophilum Gins51 (TaGins51) is critical for the tetramer formation, for its function to activate the replicative helicase (TaMCM).